Mechanisms of arsenic and fluoride release from Chacopampean sediments (Argentina). (2014) - García, M.G.; Borgnino, L.; Bia, G.; Depetris, P.J.
We have examined the sources and mechanisms that control the release of fluoride and arsenate from fluvial and loess sediments collected from the Chacopampean region, Argentina. The two types of sediment show slight differences regarding the mechanism of release. In fluvial sediments the release of fluoride seems to be controlled by the dissolution of primary F-bearing minerals, such as fluorapatite (FAp) and biotite. Much lower concentrations of As are also released from fluvial sediments under acidic conditions, owing to the dissolution of As-bearing igneous FAp. Under more alkaline conditions, the release of both anions is the result of desorption from Fe (hydr)oxide coats. In loess sediments, F and As are released by dissolution of FAp present either as detritic grains or forming thin coats onto the volcanic ash, while arsenate is preferentially desorbed from Fe (hydr)oxide coats under alkaline conditions or by competitive desorption at acidic pH.